Inleiding: ’History of computing’. Geschiedschrijving over computers en computergebruik in Nederland - van den Boogaard, Adrienne (Studium, 2008)
Along with the international trends in history of computing, Dutch contributions over the past twenty years moved away from a focus on machinery to the broader scope of use of computers, appropriation of computing technologies in various traditions, labour relations and professionalisation issues, and, lately, software.It is only natural that an emerging field like computer science sets out to write its genealogy and canonise the important steps in its intellectual endeavour. It is fair to say that a historiography diverging from such “home” interest, started in 1987 with the work of Eda Kranakis – then active in The Netherlands – commissioned by the national bureau for technology assessment, and Gerard Alberts, turning a commemorative volume of the Mathematical Center into a history of the same institute. History of computing in The Netherlands made a major leap in the spring of 1994 when Dirk de Wit, Jan van den Ende and Ellen van Oost defended their dissertations, on the roads towards adoption of computing technology in banking, in science and engineering, and on the gender aspect in computing. Here, history of computing had already moved from machines to the use of computers. The three authors joined Gerard Alberts and Onno de Wit in preparing a volume on the rise of IT in The Netherlands, the sequel of which in now in preparation in a team lead by Adrienne van den Bogaard.Dutch research reflected the international attention for professionalisation issues (Ensmenger, Haigh) very early on in the dissertation by Ruud van Dael, Something to do with computers (2001) revealing how occupations dealing with computers typically escape the pattern of closure by professionalisation as expected by the, thus outdated, sociology of professions. History of computing not only takes use and users into consideration, but finally, as one may say, confronts the technological side of putting the machine to use, software, head on. The groundbreaking works of the 2000 Paderborn meeting and by Martin Campbell-Kelly resonate in work done in The Netherlands and recently in a major research project sponsored by the European Science Foundation: Software for Europe.The four contributions to this issue offer a true cross-section of ongoing history of computing in The Netherlands. Gerard Alberts and Huub de Beer return to the earliest computers at the Mathematical Center. As they do so under the perspective of using the machines, the result is, let us say, remarkable. Adrienne van den Bogaard compares the styles of software as practiced by Van der Poel and Dijkstra: so much had these two pioneers in common, so different the consequences they took. Frank Veraart treats us with an excerpt from his recent dissertation on the domestication of the micro computer technology: appropriation of computing technology is shown by the role of intermediate actors. Onno de Wit, finally, gives an account of the development, prior to internet, of a national data communication network among large scale users and its remarkable persistence under competition with new network technologies.